A REVIEW OF THE MONOGRAPH ON SOCIAL HISTORY OF THE QIPCHAQS IN THE 9TH – 13TH CENTURIES Pilipchuk Y.V. Social history of Qipchaqs in the IX–XIII centuries. Kiev – Vinnitsa: National Pedagogical University of M.P. Dragomanov, “CREATIVITY”, 2018. - Timohin, Dmitrij Mihajlovic; Tisin, Vladimir Vladimirovic (History, Archeology and Ethnography of the Caucasus, 2020)
The present paper is a review of the monograph “Social history of Qipchaqs in the IX–XIII centuries.” by the Ukrainian researcher Y.V. Pilipchuk. The authors of the article highlight the relevance of the issue stated in the title due to the interest in this kind of works. However, upon closer examination, the content of Pilipchuk’s work turns out to be inconsistent with its title. In addition to the fact that there is a clear disproportion between relevant to social issues material and that which can be conditionally recognized as such, social problems as a whole are raised in quite a shallow and controversial way. A number of other shortcomings, relating primarily to the author’s methodology and his use of historical sources and scientific literature is also noted by the reviewers. Based on the remarks made, reviewers conclude that this work cannot be recognized as making any contribution to the study of the social history of the Qipchaqs.